1999
DOI: 10.1139/g99-033
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of homoeologous segments of the genomes of rice andArabidopsis thaliana

Abstract: Using contiguous genomic DNA sequences of Arabidopsis thaliana, we were able to identify a region of conserved structure in the genome of rice. The conserved, and presumptive homoeologous segments, are 194 kb and 219-300 kb in size in Arabidopsis and rice, respectively. They contain five homologous genes, distinguished in order by a single inversion. These represent the first homoeologous segments identified in the genomes of a dicot and a monocot, demonstrating that fine-scale conservation of genome structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Comparisons between Arabidopsis and rice, the model dicot and monocot species, respectively, showed only very small intervals of microsynteny in some regions (van Dodeweerd et al 1999;Liu et al 2001;Salse et al 2002), smaller than expected (Paterson et al 1996).…”
mentioning
confidence: 81%
“…Comparisons between Arabidopsis and rice, the model dicot and monocot species, respectively, showed only very small intervals of microsynteny in some regions (van Dodeweerd et al 1999;Liu et al 2001;Salse et al 2002), smaller than expected (Paterson et al 1996).…”
mentioning
confidence: 81%
“…For example, this comparative approach has been used to leverage genomic information from the model species Arabidopsis thaliana to related crop species (Van Dodeweerd et al 1999;Grant et al 2000;Ku et al 2000;Bevan and Walsh 2005). However, the value of comparative genomic information is inversely proportional to the evolutionary distance of the species being compared.…”
Section: Introductionmentioning
confidence: 99%
“…Few attempts to analyze genome colinearity between more distantly related species have been reported (Paterson et al, 1996;Devos et al, 1999;van Dodeweerd et al, 1999;Ku et al, 2000). The low degree of sequence homology in distantly related species hampers the unambiguous recognition of orthologous sequences, a prerequisite for studying colinearity relationships between species.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the genetic maps of Arabidopsis and different Brassica species also has revealed many colinear chromosome segments for species belonging to the Brassicaceae family (reviewed in Schmidt, 2000). The results of the first microsynteny studies using sequencelevel resolution in the Poaceae (Chen et al, 1997;Messing and Llaca, 1998;Tikhonov et al, 1999) and Brassicaceae families (Grant et al, 1998;Acarkan et al, 2000) support the view that genome colinearity can be observed at the level of genes.Few attempts to analyze genome colinearity between more distantly related species have been reported (Paterson et al, 1996;Devos et al, 1999;van Dodeweerd et al, 1999;Ku et al, 2000). The low degree of sequence homology in distantly related species hampers the unambiguous 1 These authors contributed equally to this work.…”
mentioning
confidence: 99%